Research Methodology : Types in the New Perspective - Firdaus Firdaus; Zulfadilla Zulfadilla; Fakhri Caniago (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2021)
Indonesian education requires every student to do research. Every time you carry out research, there are many methods in the manufacturing process which are commonly referred to as research methodologies, which are useful for distinguishing the types of research being carried out. There are several kinds of research methodologies including quantitative, qualitative, pure, applied, evaluation, descriptive, explanatory, experimental, non-experimental, ex post facto methodologies, surveys, case studies, and action research which have specific characteristics, weaknesses and strengths. By conducting literature studies and content analysis approaches, I got a new pattern in conducting research, namely combining two types of research, qualitative and quantitative, which were previously deemed impossible. What we have summarized in this article is for the development of Indonesia's educational civilization.